Predictors of bronchopulmonary dysplasia occurrence and severity in extremely preterm infants - Liu, Xuejing; Zhang, Wanxian; Ding, Fangrui (Frontiers in Pediatrics, 2025)
BackgroundBronchopulmonary dysplasia (BPD) is a common complication in extremely preterm infants (EPIs), and there is currently a lack of effective preventive strategies. Identifying risk factors may facilitate early interventions and improve outcomes.ObjectiveTo investigate risk factors for the occurrence and severity of BPD in EPIs and inform potential prevention strategies.MethodsWe conducted a retrospective analysis of medical records from EPIs admitted to the neonatal intensive care unit at Tianjin Central Hospital of Obstetrics and Gynecology between 2012 and 2024. BPD was diagnosed according to the 2018 revised criteria established by the National Institute of Child Health and Human Development. Multivariable logistic regression was used to identify independent risk factors.ResultsAmong 468 EPIs, 136 (29.1%) developed BPD (mild: 14.1%, moderate: 7.1%, severe: 7.9%). Independent risk factors for BPD included prolonged invasive mechanical ventilation (IMV, OR = 1.10, 95% CI 1.03–1.17), frequent red blood cell transfusions (RBCTs, OR = 1.61, 95% CI 1.30–2.01), extended antibiotic exposure (OR = 1.03, 95% CI 1.01–1.06), and hemodynamically significant patent ductus arteriosus (hsPDA, OR = 2.27, 95% CI 1.22–4.20). Prolonged IMV (OR = 1.16, 95% CI 1.06–1.27) and higher fluid balance (FB) on postnatal day 7 (OR = 1.19, 95% CI 1.05–1.34) were independent risk factors for moderate-to-severe BPD, while higher birth weight (OR = 0.99, 95% CI 0.988–0.998) was found to be a protective factor. Whole blood transfusion was associated with an increased risk of BPD (OR = 4.48, 95% CI 1.92–10.43) and moderate-to-severe BPD (OR = 4.81, 95% CI 1.24–18.63) compared to packed RBCTs. In predicting moderate-to-severe BPD, the duration of IMV (cut-off: 6.5 days) and FB on postnatal day 7 (cut-off: −7.2) demonstrated significant predictive value.ConclusionsIn conclusion, the occurrence and severity of BPD in EPIs are influenced by prolonged IMV, frequent RBCTs, fluid overload, excessive antibiotic exposure, and hsPDA. Early interventions targeting modifiable factors, such as reducing IMV duration, maintaining an appropriate negative FB on postnatal day 7, and optimizing transfusion protocols, are critical to prevent moderate-to-severe BPD.